PENGARUH OCCUPANCY RATE DAN EVENT MEETING TERHADAP PENDAPATAN HOTEL PADA GRAND ROYAL DENAI HOTEL BUKITTINGGI - Winda Sari; Anne Putri; Aries Tanno; Delfi Hurnis; Romzi Rahman (Komunitas Manajemen Kompetitif, 2026)
This study aims to examine the effect of occupancy rate and event meeting activities on hotel revenue at Grand Royal Denai Hotel Bukittinggi. A quantitative approach was employed using multiple linear regression analysis. The study utilized secondary data obtained from the hotel's operational reports covering the period from January 2023 to December 2025, consisting of occupancy rate, event meeting, and hotel revenue data. Data analysis included descriptive statistics, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results indicate that occupancy rate has a positive and significant effect on hotel revenue, with a t-value of 11.867 and a significance level of 0.000. Event meeting activities also have a positive and significant effect on hotel revenue, with a t-value of 3.988 and a significance level of 0.000. Simultaneously, occupancy rate and event meeting significantly affect hotel revenue, as indicated by an F-value of 414.490 and a significance level of 0.000. The coefficient of determination (R²) of 0.962 shows that 96.2% of the variation in hotel revenue can be explained by the two independent variables. These findings suggest that optimizing room occupancy and increasing event meeting activities are effective strategies for enhancing hotel revenue.